Sistem Informasi Reservasi Service Mobil pada Menerapkan Metode Waterfall - Risma Wati (Journal of Informatics Management and Information Technology, 2023)
The company PT. Astra International Tbk- Isuzu Medan is engaged in the automotive sector. The information system will develop a car service reservation information system in processing customer data of PT. Astra International Tbk- Isuzu Medan. In processing customer data, a media or website is needed so that the public can get information and repair vehicles quickly and accurately as expected. In this final assignment, a special website will be designed that is run with media to make it easier to record data for the company and make it easier for the public to repair their vehicles. By designing this website, it will make it easier to record data and service. With the existence of an information system designed using this sublime text application, the information system must be better than the previous system in the company.